Perbedaan Reaksi Emosional Antara Olahragawan Body Contact dan Non Body Contact - Sukadiyanto, - (Jurnal Psikologi, 2006)
This research aimed to know the diffe-rence of emotional reaction status between athletes of body contact and non body conÂ¬tact, and also aimed to know the difference of emotional reaction status between boys and girls. The research method is survey, and daÂ¬ta collecting by questionnaire which consist of seven factors, that is desire, assertiveness, sensitivity, tension control, confidence, personal accountability, and self-discipline. In each factor consist of six statement item, three positive statement and three negative statements. Research populations are all athletes in Kabupaten Sleman, and with purposive sampling technique there were 204 boys and girls. Data analyzed by analysis of variance with level of significance 5%. Result of research indicate that: (1) There are difference of emotional reaction status between an athelete of body contact and non body contact, where an athelete of body contact higher than non body contact, (2) There are difference of emotional reaction status between sportsman of boys and girls, where boys higher than girls, and (3) There is no interaction between the kind of sports and the gender on the emotional reaction status. Keywords: emotional reaction, athelete, body contact, non body contact